New Insights Into the Function of Flavohemoglobin in Mycobacterium tuberculosis: Role as a NADPH-Dependent Disulfide Reductase and D-Lactate-Dependent Mycothione Reductase - Thakur, Naveen; Sharma, Amar Nath; Hade, Mangesh Dattu; Chhaya, Ajay; Kumar, Ashwani; Jolly, Ravinder Singh; Dikshit, Kanak L. (Frontiers in Cellular and Infection Microbiology, 2022)
Mycobacterium tuberculosis (Mtb) produces an unconventional flavohemoglobin (MtbFHb) that carries a FAD-binding site similar to D-lactate dehydrogenases (D-LDH) and oxidizes D-lactate into pyruvate. The molecular mechanism by which MtbFHb functions in Mtb remains unknown. We discovered that the D-LDH-type FAD-binding site in MtbFHb overlaps with another FAD-binding motif similar to thioredoxin reductases and reduces DTNB in the presence of NADPH similar to trxB of Mtb. These results suggested that MtbFHb is functioning as a disulfide oxidoreductase. Interestingly, D-lactate created a conformational change in MtbFHb and attenuated its ability to oxidize NADPH. Mass spectroscopy demonstrated that MtbFHb reduces des-myo-inositol mycothiol in the presence of D-lactate unlike NADPH, indicating that D-lactate changes the specificity of MtbFHb from di-thiol to di-mycothiol. When M. smegmatis carrying deletion in the fhbII gene (encoding a homolog of MtbFHb) was complemented with the fhb gene of Mtb, it exhibited four- to fivefold reductions in lipid peroxidation and significant enhancement in the cell survival under oxidative stress. These results were corroborated by reduced lipid peroxidation and enhanced cell survival of wild-type M. smegmatis after overexpression of the fhb gene of Mtb. Since D-lactate is a by-product of lipid peroxidation and MtbFHb is a membrane-associated protein, D-lactate-mediated reduction of mycothiol disulfide by MtbFHb may uniquely equip Mtb to relieve the toxicity of D-lactate accumulation and protect the cell from oxidative damage, simultaneously balancing the redox environment under oxidative stress that may be vital for the pathogenesis of Mtb.